Space condition International Architecture Symposium - Riewe, Roger 1959- (Springer, 2005)
Transcripts of roundtable discussions between and interviews with the following architects, critics, and researchers : Bart Lootsma, Neil Leach, Michael Speaks, Aaron Betsky, Kari Jormakka, Xavier Costa, Zaha Hadid, Elisabeth Nèost-Kahlen, Hani Rashid, Heywon Seo, Mark Goulthorpe, Eva Grubbauer, Marie Therese Harnoncourt, Ernst J. Fuchs, Greg Lynn, Tom Verebes, Kivi Sotamaa, Michael Hensel, Christoph Pichler, Hannes Traupmann, Oliver Salway, Farshid Moussavi, Alejandro Zaera Polo, Anja Jonkhans, Chris Bagot, Mascha Veech-Kosmatschof, Stuart Veech, Jacob van Rijs, Nathalie de Vries, Nigel Coates, Philipp Tschofen, Ben van Berkel, Ross Lovegrove, Nick Bax, Bostjan Vuga, Reto Pfenninger, Bill MacDonald, Sulan Kolatan, Brett Steele, David Erdman, Marcelyn Gow, Ulrika Karlsson, Chris Perry and Tobi Schneidler.